CYTOTOXIC ANALYSIS OF CAPSAICINOID COMPOUND FROM ROTTEN AND FRESH Capsicum frutescens L. ON T47D CELLS - Abrilia, Putri Riza; Hayati, Elok Kamilah; Kadarani, Deva Krisna (Department of Chemistry, Faculty of Science and Technology, UIN Sunan Gunung Djati Bandung, 2024)
Cayenne pepper has a distinctive spicy and hot taste that indicates the presence of capsaicinoid compounds. The content of capsaicinoid compounds is thought to increase along with the level of maturity. This study aims to distinguish between the capsaicinoid content in Rotten Capsicum Frutescens (RCF) and fresh Capsicum Frutescens (FCF) samples and their use as anticancer agents. Capsaicinoid extraction was performed by using reflux extraction and the identification processes using Thin Layer Chromatography (TLC) with a chloroform:methanol eluent. Identification was conducted by using Attenuated Total Reflectance-Fourier Transform Infrared Spectroscopy (ATR-FTIR) while a cytotoxicity test on T47D breast cancer cells was conducted using the Methylthiazol Tetrazolium (MTT) assay. The results showed the presence of a capsaicinoid compound group, with Retardation Factor (Rf) values of 0.76 in RCF and 0.72 in FCF, as well as orange spots due to its reaction to Dragendorff's reagent. ATR-FTIR analysis was able to identify some of typical functional groups typical of capsaicinoid, including -OH, CH3, CH2 (stretching), C=O, C=C, -CH2- (bending), C-N, C-O, O-CH3, and -NH with the intensity value of RCF greater than FCF. The cytotoxicity test results showed that the Inhibition Concentration (IC50) value for RCF isolates was 512.37 µg/mL, while for FCF isolates was1386.82 µg/mL. These results indicate that capsaicinoid isolates from RCF have a higher cytotoxicity compared to isolates from FCF. A higher IC50 value corresponds to lower cytotoxic activity.